Hubungan antara Leader Member Exchange dan Budaya Learning Organization dengan Komitmen Organisasi - , PRAYUDIASTUTI SHINTA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Globalization era was challenging employees to work more effectively and adapt to various changes occurred within an organization. It might be fulfilled due to the large number of employees who possessed high commitment to organization. They were the greatest resources that w priceless for the organization. The purpose of the study was to examine the correlation between leader member exchange and organizational learning culture to organizational commitment. Hypothesis proposed in the study was that there was positive correlation between leader member exchange and organizational learning culture to organizational commitment. The study was a field research that used quantitative methodology and questionnaire as instrument to collect data. Questionnaires used in the study were leader member exchange questionnaire, organizational learning culture questionnaire, and organizational commitment questionnaire. Data gained in the study was further analyzed using double regression analysis. Result of the data analysis of total 138 respondents showed that leader member exchange and organizational learning variables altogether provided contribution as much as 40,2% towards organizational commitment with F score =45,469 and p<0,01.